Show Me the Amenity: Are Higher-Paying Firms Better All Around? - Jason Sockin (Center for Economic Studies and ifo Institute (CESifo), 2022)
Do firms that pay more offer better amenities, or does the greater pay compensate for worse amenities? Using matched U.S. employee-employer data, this paper estimates the joint distribution of wages, amenities, and job satisfaction across firms. Fifty amenities are captured applying topic modeling to workers' free-response descriptions of their jobs. Three main findings emerge. First, higher-paying firms offer better amenities. Second, employees value amenities: one-third have a more pronounced effect on satisfaction than pay. Third, since workers are willing to pay for satisfaction and because the covariance between amenities and wages is sufficiently high, amenities widen compensation dispersion across firms.
Keywords: J01; J32; M50; 330; job amenities; job satisfaction; inequality